(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
In today’s world, it is becoming increasingly important the teachings and discussions of the links between technology and how it can have an impact in our society. One device that has been making the news lately is the breathalyzer, currently being used to enforce the “Lei Seca” Operation. The study of how the breathalyzer works, if added into the school curriculum, can help students expand their understanding of many classes such as Chemistry, Physics, Math, Biology and History, helping close the gap between science, technology and society. Most importantly, it can also help students take a leadership role in the prevention and the dangers of Drinking and Driving. This study takes a look at the scientific characteristics of different types of breathalyzers and its potential addition as an interdisciplinary course while still following the parameters of educational guidelines.